International experience of features of food security (Journal of Economic Research & Business Administration, 2016)
The issue of food security is a priority of the state policy in different countries, and the focus of research. In turn, in the process of developing an effective strategy for food security analysis of the important role played by the advanced experience of foreign countries in the consideration of global trends. In this article, the problem of food security is seen as an im-portant component of economic security of the country; to determine the meaning and content of the concept of food security and food security are analyzed model of international best practice.
Keywords: food security; globalization; agriculture; competitiveness; agricultural products; production.